PERAN PENDIDIKAN KEWIRAUSAHAAN DAN DUKUNGAN AKADEMIK DALAM MENINGKATKAN INTENSI BERWIRAUSAHA - Alif Putra Suandi Alif; Henky Lisan Suwarno (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2022)
Entrepreneurship has been considered to be one of the effective solutions according to the effort to reduce the high unemployment rate in Indonesia. This study aims to examine the effect of entrepreneurship education and academic support on the intensity of entrepreneurship. This research was conducted on students of the Maranatha Christian University Management Study Program. The type of research in this research is quantitative. Data in collecting questionnaire techniques and data processing using SmartPLS. The results showed that the variables of entrepreneurship education and academic support influenced the intensity of student entrepreneurship.